SOME FACTORS THAT INFLUENCE ON DEBT POLICY - Wijaya, Tony; Hastuti, Rini Tri (International Journal of Application on Economics and Business, 2024)
A company is considered at risk if it has a large portion of debt in its capital structure, but conversely, if a company uses little or no debt at all, the company is considered unable to take advantage of additional external capital that can improve the company's operations. Based on these reasons, managers are required to be more careful in determining debt policies in their companies. Meanwhile, according to the trade of theory, the higher the debt, the higher the bankruptcy burden. Based on the general assumptions of the pecking order theory and trade of theory, the use of debt should be low. However, many companies still pay high debt. From these reasons, research on debt policy needs to be examined. This study aims to empirically prove the impact of company characteristics, asset structure, and profitability on debt policies in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The data used in this study were 28 companies. The sample used was 84 sample data selected using purposive sampling method which were processed using EViews version 12. The result of this study indicates that all independent variables simultaneously have no significant impact on debt policy as shown by the results of the F test. The results of the T test explain that company characteristics have a negative and insignificant impact on debt policy, asset structure has a negative and insignificant impact on debt policy, and profitability has a positive and insignificant impact on debt policy.